Preparation and characterisation of curcumin‐loaded pea protein‐zein nanocomplexes using pH‐driven method. (11th March 2022) - Zhao, Yilin; Han, Xinxin; Yin, Huanhuan; Li, Qi; Zhou, Jingyi; Zhang, Hao; Zhang, Wenge; Zhao, Chengbin; Liu, Jingsheng
Summary: The nanocomplexes of hydrophilic pea protein (Pp) and hydrophobic zein were prepared to encapsulate curcumin (Cur) by the pH‐driven method. The properties of pea protein‐zein complex were affected by many factors, of which mass ratio was one of the most important factors. The nanocomplexes with a mass ratio Pp to zein of 8:2 showed a smaller size (near 100 nm) and a higher stability than individual Pp nanoparticles. The solubility of Cur was significantly improved by the nanocomplexes prepared by this method. In neutral aqueous solution, the solubility of Cur encapsulated with the nanocomplex reached 652 μg mL −1, and the nanocomplexes had excellent re‐dispersibility. The main forces for the formation of nanocomplexes were hydrophobic interactions and hydrogen bonds, and the Cur existed in amorphous state in the nanocomplexes. The Cur coated with protein complexes had higher storage stability and thermal stability than Cur loaded with single protein, indicating the stronger protection on Cur provided by protein complexes. Furthermore, the nanocomplexes exhibited an improved antioxidant activity after in vitro simulated digestion. Thus, the nanocomplexes prepared by a simple and safe pH‐driven method could be used for functional protection and delivery of hydrophobic bioactive compounds. Abstract : The structure, stability and physicochemical property of curcumin loaded pea protein‐zein nanocomplexes prepared using pH‐driven method.